Bilateral adrenal infarction and insufficiency associated with antiphospholipid syndrome and surgery: a case report - Yoshihito Iijima; Masahito Ishikawa; Nozomu Motono; Hidetaka Uramoto (International Journal of Emergency Medicine, 2023)
Abstract Background Antiphospholipid syndrome causes systemic arterial and venous thromboses due to the presence of antiphospholipid antibodies. Adrenal insufficiency is a rare complication of antiphospholipid syndrome that may result in fatal outcomes if left untreated. Therefore, we report adrenal insufficiency as a rare complication of bilateral adrenal infarction associated with antiphospholipid syndrome and trauma surgery. Case presentation A 64-year-old male patient underwent surgery for a left traumatic hemothorax. He concurrently had antiphospholipid syndrome and was receiving warfarin. Postoperatively, the patient complained of severe lumbar back pain despite resuming anticoagulation therapy, and he experienced paralytic ileus and shock. Abdominal contrast-enhanced computed tomography revealed adrenal swelling and increased surrounding retroperitoneal adipose tissue density. Diffusion-weighted abdominal magnetic resonance imaging showed high-intensity areas in the bilateral adrenal glands. Cortisol and adrenocorticotropic hormone levels were 3.30 μg/dL and 185.1 pg/dL, respectively. Subsequently, the patient was diagnosed with bilateral adrenal infarction and acute adrenal insufficiency, and hydrocortisone was immediately administered. Adrenal insufficiency improved gradually, and the patient was discharged after initiating steroid replacement therapy. Conclusions The timing of postoperative anticoagulant therapy initiation remains controversial. Therefore, adrenal insufficiency due to adrenal infarction should be monitored while anticoagulant therapy is discontinued in patients with antiphospholipid syndrome.